2022
DOI: 10.4293/jsls.2022.00027
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Achalasia: From Laparoscopic to Robotic Heller Myotomy and Dor Fundoplication

Abstract: Objective: Laparoscopic Heller myotomy and Dor fundoplication has become the gold standard in treating esophageal achalasia and robotic surgical platform represents its natural evolution. The objective of our study was to assess durable long-term clinical outcomes in our cohort.Methods and Procedures: Between June 1, 1999 and June 30, 2019, 111 patients underwent minimally invasive treatment for achalasia (96 laparoscopically and 15 robotically). Fifty-two were males. Mean age was 49 years (20 -96). Esophageal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…[14] Early cases series on robotic Heller myotomies report excellent post-operative symptom relief, noninferior to that of the established laparoscopic approach with acceptable intraoperative and postoperative complication rate. [15][16][17][18][19][20][21][22][23] In fact, Kim et al presented superior average length of myotomy and improved symptom control with the robotic approach, while Raja et al demonstrated superior long-term symptom relief and decreased reintervention rate when comparing robotic to laparoscopic myotomy. [16,23] A number of studies report reduced incidence of intraoperative complication rate, mainly mucosal tears while using the robotic platform [15,18,20,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[14] Early cases series on robotic Heller myotomies report excellent post-operative symptom relief, noninferior to that of the established laparoscopic approach with acceptable intraoperative and postoperative complication rate. [15][16][17][18][19][20][21][22][23] In fact, Kim et al presented superior average length of myotomy and improved symptom control with the robotic approach, while Raja et al demonstrated superior long-term symptom relief and decreased reintervention rate when comparing robotic to laparoscopic myotomy. [16,23] A number of studies report reduced incidence of intraoperative complication rate, mainly mucosal tears while using the robotic platform [15,18,20,22].…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23] In fact, Kim et al presented superior average length of myotomy and improved symptom control with the robotic approach, while Raja et al demonstrated superior long-term symptom relief and decreased reintervention rate when comparing robotic to laparoscopic myotomy. [16,23] A number of studies report reduced incidence of intraoperative complication rate, mainly mucosal tears while using the robotic platform [15,18,20,22]. According to the authors of these studies, this is mainly attributed to the more precise three-dimensional vision combined with more elegant tissue manipulation of the robotic platform.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of NGT for achalasia surgery is still controversial. Many authors routinely place NGT after this surgery, others insert it before, but they say nothing about its removal [54][55][56]. However, it is not clear if other authors use it [57][58][59][60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…The patient was diagnosed with achalasia and underwent Heller myotomy after prehabilitation with fluid and electrolyte replacement and parenteral nutrition. The decision making regarding treatment must be individualized, and the participation of a multidisciplinary team is always advisable [45][46][47][48]55]. While patients are waiting for an expeditious solution to their disease, some dietary measures should be adopted.…”
Section: Achalasiamentioning
confidence: 99%